EVALUASI MUTU FISIK DAN KIMIA KULIT BOX SAMAK KROM SEBAGAI BAHAN UPPER SEPATU BERDASARKAN ISO 20942:2019 - Himawan Santoso; Wahyu Fajar Winata (Politek ATK Yogyakarta Press, 2026)
Chrome-tanned box leather is one of the primary materials used for shoe uppers due to its excellent strength, flexibility, and durability. The quality of upper leather is determined by its physical and chemical characteristics, which must comply with established standards to ensure the production of high-quality footwear. This study aimed to evaluate the physical and chemical quality of chrome-tanned box leather based on the requirements of ISO 20942:2019 as the reference standard for shoe upper leather. The physical parameters evaluated included leather thickness, leather area, and defect percentage, while the chemical parameters comprised moisture content, ash content, fat content, chromium oxide (Cr₂O₃) content, pH value, and ΔpH. All tests were conducted according to the relevant ISO standard methods, including ISO 2589, ISO 4045, ISO 4047, ISO 4048, ISO 4684, and ISO 5398. The data were analyzed descriptively by comparing the test results with the requirements specified in ISO 20942:2019 and supported by findings from previous studies. The results showed that the chrome-tanned box leather had a thickness of 1.58 mm, a leather area of 17 ft², a defect percentage of 15%, a moisture content of 15.00%, an ash content of 5.18%, a fat content of 5.16%, a chromium oxide (Cr₂O₃) content of 3.09%, a pH ranging from 3.90 to 4.05, and a ΔpH value of 0.13. All evaluated parameters complied with the quality requirements specified in ISO 20942:2019, indicating that the tested chrome-tanned box leather is suitable for use as shoe upper material. The findings provide valuable information regarding the conformity of chrome-tanned box leather quality with international standards and may serve as a reference for quality control practices in the leather tanning industry. In addition, the physical and chemical characteristics of the evaluated leather indicate its potential to support ergonomic aspects of footwear products through improved material flexibility, user comfort, chemical safety, and manufacturing efficiency.